2016
DOI: 10.1016/j.jclinepi.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Measuring drug exposure: concordance between defined daily dose and days' supply depended on drug class

Abstract: Objective To determine the concordance between two methods to measure drug exposure duration from pharmacy claims data. Study design and setting We conducted a cohort study using 2002–2007 US Medicaid data. Initiators of eight drug groups were indentified: statins, metformin, atypical antipsychotics, warfarin, proton pump inhibitors (PPIs), angiotensin converting enzyme (ACE)-inhibitors, non-steroidal anti-inflammatory drugs (ns-NSAIDs) and coxibs. For each patient, we calculated two measures of exposure dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 17 publications
(17 reference statements)
0
46
0
1
Order By: Relevance
“…Because dose requirements depend on individual clearance of the drug and are often influenced by age, estimations using individual parameters for dose calculations appear more promising than strategies assuming standard doses for all patients (e.g., OTAD or DDD). Thus, it may be speculated that drug consumption expressed as DDD may lead to considerable miscalculations in such situations …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because dose requirements depend on individual clearance of the drug and are often influenced by age, estimations using individual parameters for dose calculations appear more promising than strategies assuming standard doses for all patients (e.g., OTAD or DDD). Thus, it may be speculated that drug consumption expressed as DDD may lead to considerable miscalculations in such situations …”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be speculated that drug consumption expressed as DDD may lead to considerable miscalculations in such situations. 33,34 In this study, we compared different approximations of drug prescription durations in claims data with respect to accuracy and impact on clinical endpoints. M&S revealed that longitudinally averaging drug utilization was the method yielding the most accurate estimations regarding several measures of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…As patients may discontinue or restart drug therapy, the analyses assumed that a patient's exposure to DMARDs contributed both cumulatively and continuously to their long-term risk of dementia. Defined daily dose (DDD) is the assumed average maintenance dose per day for a drug used for its primary usage in adults [22]. To investigate the effect of dose, the cumulative use of DMARDs was calculated as the total prescribed DDD (i.e., the same as the total dispensed DDD).…”
Section: Cumulative Exposure Of Dmardsmentioning
confidence: 99%
“…[31] The method of calculating a days' supply variable using the DDD and its concordance with the conventional days' supply variable is outlined in our previous work. [32] Monthly PDCs were calculated for each patient, running consecutively from cohort entry to the end of follow up for each individual. If a dispensing occurred before the previous dispensing ran out, the new dispensing was assumed to begin the day after the end of the prior dispensing and the diary was adjusted accordingly.…”
Section: Study Endpointsmentioning
confidence: 99%